PENENTUAN KAPASITAS SIMPAN SHALE GAS PADA SUMUR “R26”, LAPANGAN “RKO - Ohorella, Ramdhan; Effendi, Dahrul; Triaji, Nandang (Petro : Jurnal Ilmiah Teknik Perminyakan, 2024)
Global demand for oil and gas is projected to increase by 6% from 2022 to 2028, reaching 105.7 million barrels per day (bopd), driven by strong demand from the petrochemical and aviation sectors. Consequently, exploration is needed to discover new oil and gas reserves, with attention shifting to unconventional resources, considering the depletion and challenges in finding conventional reserves. This study aims to analyze the adsorption behavior of five shale rock samples from the "RKO" field, well "R26," determine the maximum adsorption values using Langmuir isotherm modeling, and evaluate the effect of depth on adsorption capacity. The data used in this research includes proximate analysis and adsorption isotherm data to illustrate the adsorption curves that occur in the samples. Based on the test results, it was found that the five shale samples from well "R26," namely samples RM-001, RM-002, RM-003, RM-004, and RM-005, follow a Type 1 adsorption isotherm pattern, where the amount of adsorbate increases linearly with increasing pressure. Furthermore, the Langmuir isotherm modeling results for the samples indicate a maximum adsorption pressure of 2851 psi, with maximum adsorption volumes of 2.35 m³/t for RM-001, 2.44 m³/t for RM-002, 2.42 m³/t for RM-003, 2.48 m³/t for RM-004, and 2.42 m³/t for RM-005. The test results also show that depth variation does not affect the volume and adsorption capacity.